Implikasi Yuridis Penetapan Covid-19 Sebagai Bencana Nasional Dalam Pelaksanaan Kontrak - Muhammad Fajar Hidayat; Desi Sommaliagustina (Jurnal Selat, 2020)
Corona Virus Disease 2019 or COVID-19 has been determined by President Joko Widodo to become a National Disaster with Presidential Decree No. 12 of 2020 concerning Determination of Non-Disaster in the Spread of Corona Virus Disease 2019 (COVID-19) as a National Disaster in Jakarta on April 13, 2020. The President has issued Presidential Decree 11 of 2020 concerning Establishment of Community Health Emergency COVID-19. The spread of Corona Virus Disease 2019 (COVID-19) has had an impact on negative global economic growth, including engagement. Parties who cannot fulfill their achievements in an engagement because the covid-19 pandemic does not necessarily classify the condition of the covid-19 pandemic as a state of overmacht or force majeure. Must be assessed on a case by case basis in accordance with the circumstances and factual conditions that occur. Except if the parties in a contract agreed upon with the parties have described in detail about what is qualified as a force majeure.